A phylogenetic study of Chinese Velarifictorus Randell, 1964 based on COI gene with describing one new species (Orthoptera: Gryllidae: Gryllinae) - Chen, Guang-Yu; Shen, Chu-Ze; Liu, Yun-Fei; Liao, Wang; He, Zhu-Qing (Zootaxa, 2018)
Eight species of genus Velarifictorus Randell, 1964 have been recorded from China prior to this study. Here we describe one new species, Velarifictorus dianxiensis He sp. nov. from western Yunnan. COI genes of Velarifictorus spp. were used to reconstruct a phylogenetic tree for confirming the relationships of these species. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).